Long-term survival and health-related quality of life after in-hospital cardiac arrest. (October 2021) - Schluep, Marc; Hoeks, Sanne Elisabeth; Blans, Michiel; van den Bogaard, Bas; Koopman-van Gemert, Ankie; Kuijs, Cees; Hukshorn, Chris; van der Meer, Nardo; Knook, Marco; van Melsen, Trudy; Peters, René; Perik, Patrick; et al.
Abstract: Introduction: In-hospital cardiac arrest (IHCA) is an adverse event associated with high mortality. Because of the impact of IHCA more data is needed on incidence, outcomes and associated factors that are present prior to cardiac arrest. The aim was to assess one-year survival, patient-centred outcomes after IHCA and their associated pre-arrest factors. Methods: A multicentre prospective cohort study in 25 hospitals between January 1st 2017 and May 31st 2018. Patients ≥ 18 years receiving cardiopulmonary resuscitation (CPR) for IHCA were included. Data were collected using Utstein and COSCA-criteria, supplemented by pre-arrest Modified Rankin Scale (MRS, functional status) and morbidity through the Charlson Comorbidity Index (CCI). Main outcomes were survival, health-related quality of life (HRQoL, EuroQoL) and functional status (MRS) after one-year. Results: A total of 713 patients were included, 64.5% was male, median age was 63 years (IQR 52–72) and 72.8% had a non-shockable rhythm, 394 (55.3%) achieved ROSC, 231 (32.4%) survived to hospital discharge and 198 (27.8%) survived one year after cardiac arrest. Higher pre-arrest MRS, age and CCI were associated with mortality. At one year, patients rated HRQoL 72/100 points on the EQ-VAS and 69.7% was functionally independent. Conclusion: One-year survival after IHCA in this study is 27.8%, which is relatively high compared to previous studies. Survival is associated with a patient's pre-arrest functional status and morbidity. HRQoL appears acceptable, however functional rehabilitation warrants attention. These findings provide a comprehensive insight in in-hospital cardiac arrest prognosis.